(untitled) (ACME, 2021)
Some speeches of Dion of Prusa attest to the themes that were at the center of the political debate in Prusa and other cities of the province of Bithynia. Dion’s so-called civic speeches often refer to the building program which Dion himself proposed and partially funded with the aim of embellishing his city. However, his proposal soon became reason of political attack as Dion’s political opponents accused him for not having completed the promised buildings and for having destroyed large portions of the city with the only scope of making space for his building program. The analysis of the contemporary building legislation in Rome shows how often such kind of problems affected Rome herself and other cities of the Empire, which led the emperors to frequently legislate in this regard.